TRPV1 Activation Attenuates High-Salt Diet-Induced Cardiac Hypertrophy and Fibrosis through PPAR-δ Upregulation - Feng Gao; Yi Liang; Xiang Wang; Zongshi Lu; Li Li; Shanjun Zhu; Daoyan Liu; Zhencheng Yan; Zhiming Zhu (PPAR Research)
High-salt diet-induced cardiac hypertrophy and fibrosis are associated with increased reactive oxygen species production. Transient receptor potential vanilloid type 1 (TRPV1), a specific receptor for capsaicin, exerts a protective role in cardiac remodeling that resulted from myocardial infarction, and peroxisome proliferation-activated receptors δ (PPAR-δ) play an important role in metabolic myocardium remodeling. However, it remains unknown whether activation of TRPV1 could alleviate cardiac hypertrophy and fibrosis and the effect of cross-talk between TRPV1 and PPAR-δ on suppressing high-salt diet-generated oxidative stress. In this study, high-salt diet-induced cardiac hypertrophy and fibrosis are characterized by significant enhancement of HW/BW%, LVEDD, and LVESD, decreased FS and EF, and increased collagen deposition. These alterations were associated with downregulation of PPAR-δ, UCP2 expression, upregulation of iNOS production, and increased oxidative/nitrotyrosine stress. These adverse effects of long-term high-salt diet were attenuated by chronic treatment with capsaicin. However, this effect of capsaicin was absent in TRPV1−/− mice on a high-salt diet. Our finding suggests that chronic dietary capsaicin consumption attenuates long-term high-salt diet-induced cardiac hypertrophy and fibrosis. This benefit effect is likely to be caused by TRPV1 mediated upregulation of PPAR-δ expression.